2014
DOI: 10.20344/amp.5257
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Rivaroxaban for the Treatment and Long-Term Prevention of Venous Thromboembolism in Portugal

Abstract: Introduction: Venous thromboembolism is a burden on healthcare systems. The aim of this analysis was to project the long-term costs and outcomes for rivaroxaban compared to standard of care (enoxaparin/warfarin) in Portugal for the treatment and secondary prevention of venous thromboembolism. Material and Methods: A Markov model was developed using event rates extracted from the EINSTEIN trials supplemented with literature-based estimates of longer-term outcomes. Core outcomes included per patient costs and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…All of them suggested that DOACs are costeffective relative to VKA. 100,[104][105][106][107][108][109][110][111][112][113][114][115][116] Finally, we considered DOACs to be acceptable and feasible to implement in most scenarios. However, given their cost, some patients might not be able to afford them.…”
Section: Other Etd Criteria and Considerationsmentioning
confidence: 99%
“…All of them suggested that DOACs are costeffective relative to VKA. 100,[104][105][106][107][108][109][110][111][112][113][114][115][116] Finally, we considered DOACs to be acceptable and feasible to implement in most scenarios. However, given their cost, some patients might not be able to afford them.…”
Section: Other Etd Criteria and Considerationsmentioning
confidence: 99%
“…Recent cost-effectiveness analyses have shown cost savings associated with rivaroxaban in the treatment of VTE in the US 26,27 , Portugal 28 , and the UK 29 . The aim of the current study is to evaluate the health economic consequences of treating acute VTE patients with rivaroxaban compared to treatment with LMWH/VKA, viewed from the Dutch societal perspective; with the inclusion of loss of productivity and patient travel costs being rather specific to the Dutch guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Cost analyses from other countries also suggested a better profile for rivaroxaban than warfarin/ LMWH in both DVT treatment and prophylaxis. 6,13,16,17 In those analyses based on a Markov model, all DVT-related costs were considered. In Turkey, such an analysis does not seem feasible, however, owing to inadequate data.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other countries, the acquisition cost of rivaroxaban is higher than warfarin also in Turkey. 5,13 The annual cost of rivaroxaban use for each patient is nearly 15-fold higher as compared to warfarin. Therefore, drug acquisition cost is the most important determinant of the overall cost of DVT treatment with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%